Da questão agrária brasileira: uma análise sobre o debate da década de 60 e 70 - Silva, Tiago Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
This monograph object of analysis is the agriculture modernization in Brazil between 1960 and 1980, highlighting the discussion of the economic and politic ideas around the Brazilian agrarian question. The first parte presents an introduction about this issue and the theoretical positions, as well as social and economic implications for the development of the productive forces on rural areas. Nevertheless, reflections of its development to the economy as a whole, highlighting the way the income distribution and concentration was realized. On the second part its presented the agriculture modernization Project on the centralized militar government point of view, by the propositions of that time Agriculture Minister, Antônio Delfim Netto. The approach is made through the proposals precreeded by the Rural Worker Statute and the Land Statute, before the Military Coup, with its news counterpoints settled in law by the Agriculture Modernization Project installed in 1964; the concessions of funding grants and subsidized credits; the relationship between the authoritarian State and the militarization of the land conflicts. The third part deals with the salary dinamics, income and profit on the modernized rural economy created by the agroindustrial productions system. Lastly the conclusion cross the economic and social results of the agrarian question evolution, to the Brazilian agriculture modernization on income distribution

O objeto de análise deste trabalho é a modernização da agricultura no Brasil entre 1960 e 1980, ressaltando o debate das idéias econômicas e políticas envolvidas na questão agrária brasileira. A primeira parte apresenta uma introdução a respeito da questão agrária e os posicionamentos teóricos, bem como suas implicações econômicas e sociais para o desenvolvimento das forças produtivas no meio rural. Não obstante, os reflexos do seu desenvolvimento para a economia como um todo, destacando a maneira como era realizada a distribuição e a concentração da renda. Na segunda parte é apresentado o projeto de modernização da agricultura do ponto de vista do governo militar centralizado nas proposições do então ministro da fazenda Antônio Delfim Netto. A abordagem é feita através: das propostas precedidas pelo Estatuto do Trabalhador Rural e do Estatuto da Terra, anteriores ao golpe militar, com seus novos contrapontos estabelecido em lei pelo projeto de modernização da agricultura implantado em 1964; das concessões de financiamentos e crédito subsidiado; da relação do Estado autoritário e a militarização dos conflitos fundiários. A terceira parte trata da dinâmica do salário, da renda e do lucro na economia rural modernizada criada pelo sistema agroindustrial de produção. Já a conclusão versa sobre os resultados econômicos e sociais da evolução da questão agrária à modernização da agricultura brasileira na distribuição renda
Keywords: Economia; Agricultura; Desenvolvimento econômico; Desenvolvimento social